Connectivity changes between slopes and Umiujaq River, Nunavik, Canada ... : Changement de connectivité entre les versants et la rivière d’Umiujaq, Nunavik, Canada ... - Anne-Julia Rollet; Vincent Filion; Najat Bhiry; Armelle Decaulne (LabEx DRIIHM, 2024)
Over the last decades, the socio-ecosystem of Umiujaq has encountered drastic changes due to climatic and anthropogenic impacts. Permafrost degradation transfers water and suspended sediments towards the Umiujaq River. Aerial photos and satellite images document the main characteristics of environmental changes on the entire watershed. During the last year, we quantified the landform evolutions along the river, and tracked bank and slope instabilities that connect to the river. Despite a global low lateral mobility, the course and flow of the Umiujaq River evolve according to the capture of thermokarst pools that develop on its banks. Shrub development in the valley and beaver dams are also factors in modifying river processes. Fieldwork focused on a landslide deposit corresponding to a recurrent dynamic, that impacts the river morphology. Sampling was carried out in the deposits and in the source-area, to contribute to the contaminant documentation of the area; trees sampling was collected for ... : Au cours des dernières décennies, le socio-écosystème d'Umiujaq a subi des changements drastiques dus aux impacts climatiques et anthropiques. La dégradation du pergélisol transfère l'eau et les sédiments en suspension vers la rivière Umiujaq. Les photos aériennes et les images satellites documentent les principales caractéristiques des changements environnementaux sur l'ensemble du bassin versant. Au cours de l'année écoulée, nous avons quantifié l'évolution du relief le long de la rivière et suivi les instabilités des berges et des pentes qui se connectent à la rivière. Malgré une faible mobilité latérale globale, le cours et le débit de la rivière Umiujaq évoluent en fonction de la capture des mares thermokarstiques qui se développent sur ses rives. Le développement d'arbustes dans la vallée et les barrages de castors sont également des facteurs qui modifient les processus fluviaux. Le travail de terrain s'est concentré sur un dépôt de glissement de terrain correspondant à une dynamique récurrente, qui a ...